1977
DOI: 10.1159/000240981
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response to Fasting in Experimental Intrauterine Growth Retardation Induced by Surgical and Nonsurgical Maternal Stress

Abstract: Experimental intrauterine growth retardation was produced in two groups of neonatal rats by maternal sham surgery or by maternal obligatory exercise during the last 5 days of gestation (forced swim). Both experimental groups of neonates had lower plasma glucose and higher plasma insulin levels than controls after a 4-hour fast. Fetal stunting may be produced by a variety of maternal stresses in the rat and may be associated with alterations in the hormonal and glycemic response to fasting. Studies of the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…Despite free access to food, maternal exercise during pregnancy had adverse effects on the birth weight of pups. The intra-uterine growth retardation observed in the present study supports previous findings (Terada, 1974;Levitsky et al 1977;Uriu-Hare et al 1989). The competition between maternal exercising muscles and the fetus for substrates may have resulted in a decreased availability of these substrates for normal fetal growth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite free access to food, maternal exercise during pregnancy had adverse effects on the birth weight of pups. The intra-uterine growth retardation observed in the present study supports previous findings (Terada, 1974;Levitsky et al 1977;Uriu-Hare et al 1989). The competition between maternal exercising muscles and the fetus for substrates may have resulted in a decreased availability of these substrates for normal fetal growth.…”
Section: Discussionsupporting
confidence: 93%
“…Exercise increases energy expenditure and exercise or physical work during pregnancy is thought to be a predisposing factor to premature labour, low-birth-weight babies and increased infant mortality rates (Naeye & Peters, 1982). Adverse effects of maternal exercise during pregnancy and lactation on fetal outcome and postnatal growth in animals have been reported (Terada, 1974;Levitsky et al, 1977;Parizkova, 1979;Jenkins & Ciconne, 1980;Uriu-Hare et al 1989). A preliminary study conducted in our laboratory indicated that the adverse effects of maternal exercise during pregnancy and lactation on fetal and pup growth last beyond the weaning period causing irreversible growth retardation in rats (Pinto & Shetty, 1990).…”
mentioning
confidence: 99%
“…2). Although this just failed to reach statistical significance it should be noted that sham surgery has been shown to influence growth rate in utero (17) and in some studies is associated with a decrease in birth weight (18). Although in the present study, 24-h weight was not significantly reduced in the sham surgery group, a temporary drop in fetal weight cannot be completely excluded.…”
Section: Discussioncontrasting
confidence: 82%
“…Fetal weight was unaffected in the normal weight gain group of others (7,32,33). The absence of IUGR in the normal weight expressed as percent change from controls.…”
Section: Discussionmentioning
confidence: 88%